Enhancing Creative Thinking And Communication Skills Through Engineering Design Process (EDP) Learning Model: A Case Study - Mellyatul Aini; Meliyana Aini (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2023)
The aim of this study is to determine the effect of the Engineering Design Process (EDP) learning model in improving 21st Century skills, students' creative thinking and communication skills on the subject of basic concept of genetics. Using a mixed-methods (qualitative and quantitative) approach, the authors aimed at identifying the effect of the EDP learning model implemented on Science Education undergraduate students, Manado State University. Our proposed learning model developed students’ creative thinking and communication skills in one class with 20 participants who enrolled in a course in General Biology I. Data collection techniques were used to assess creative thinking and communication skills, using written test data and observation data, respectively. The effectiveness of the EDP learning model is confirmed by calculating the average overall score of students' creative thinking assessment of 88,44% with an excellent category. Similarly, the results of student collaboration skills showed a score of 82,19% also with an excellent category. Based on these results, it was revealed that students' creative thinking and communication skills could be increased by using the EDP learning model.